Radiofrequency transmit calibration: A multi‐center evaluation of vendor‐provided radiofrequency transmit mapping methods. Issue 6 (15th April 2019) - Bliesener, Yannick; Zhong, Xinran; Guo, Yi; Boss, Michael; Bosca, Ryan; Laue, Hendrik; Chung, Caroline; Sung, Kyunghyun; Nayak, Krishna S.
Abstract : Purpose: To determine the accuracy and test‐retest repeatability of fast radiofrequency (RF) transmit measurement approaches used in Dynamic Contrast Enhanced Magnetic Resonance Imaging (DCE‐MRI). Spatial variation in the transmitted RF field introduces bias and increased variance in quantitative DCE‐MRI metrics including tracer kinetic parameter maps. If unaccounted for, these errors can dominate all other sources of bias and variance. The amount and pattern of variation depend on scanner‐specific hardware and software. Methods: Human tissue mimicking torso and brain phantoms were constructed. RF transmit maps were measured and compared across eight different commercial scanners, from three major vendors, and three clinical sites. Vendor‐recommended rapid methods for RF mapping were compared to a slower reference method. Imaging was repeated at all sites after 2 months. Ranges and magnitude of RF inhomogeneity were compared scanner‐wise at two time points. Limits of Agreement of vendor‐recommended methods and double‐angle reference method were assessed. Results: At 3 T, B1 + inhomogeneity spans across 35% in the head and 120% in the torso. Fast vendor provided methods are within 30% agreement with the reference double angle method for both the head and the torso phantom. Conclusions: If unaccounted for, B1 + inhomogeneity can severely impact tracer‐kinetic parameter estimation. Depending on the scanner, fast vendor provided B1 + mapping sequences allow unbiased and reproducible measurements of B1 + inhomogeneity to correct for this source of bias.